Pathological Mucus and Impaired Mucus Clearance in Cystic Fibrosis Patients Results from Increased Concentration, not altered pH - Hill, David B (Eur Respir J, 2018)
Cystic fibrosis (CF) is a recessive genetic disease that is characterized by airway mucus plugging and reduced mucus clearance. There are currently alternative hypotheses that attempt to describe the abnormally viscous and elastic mucus that is a hallmark of CF airways disease, including: a) loss of cystic fibrosis transmembrane regulator (CFTR)-dependent airway surface volume (water) secretion, producing mucus hyper-concentration-dependent increased viscosity; and b) impaired bicarbonate secretion by CFTR, producing acidification of airway surfaces and increased mucus viscosity. A series of experiments were conducted to determine the contributions of mucus concentration vs. pH to the rheological properties of airway mucus across length scales from the nanoscopic to macroscopic. Our results showed that, for length scales greater than the nanoscopic, i.e., those relevant to mucociliary clearance, the effect of mucus concentration dominated over the effect of airway acidification. Our data also showed that mucus hydration and chemical reduction of disulfide bonds that connect mucin monomers are more promising therapeutic approaches than alkalization.